Disorder Contained Mental Breakdown and the Modern Prison in England and Ireland, 1840 - 1900 - Cox, Catherine (Social Sciences, 2022)
A major study into mental disorder in English and Irish prisons between 1840 and 1900, Disorder Contained investigates the relationship between prison regimes and mental distress, the complex role of prison medical officers in identifying and mediating mental illness and prisoners' experiences of mental breakdown.